The Synergy between Zinc and Antimicrobial Peptides: An Insight into Unique Bioinorganic Interactions - Donaghy, Caroline; Javellana, Jose Gabriel; Hong, Young-Jin; Djoko, Karrera; Angeles-Boza, Alfredo M. (Molecules, 2025)
Antimicrobial peptides (AMPs) are essential components of innate immunity across all species. AMPs have become the focus of attention in recent years, as scientists are addressing antibiotic resistance, a public health crisis that has reached epidemic proportions. This family of peptides represents a promising alternative to current antibiotics due to their broad-spectrum antimicrobial activity and tendency to avoid resistance development. A subfamily of AMPs interacts with metal ions to potentiate antimicrobial effectiveness, and, as such, they have been termed metalloAMPs. In this work, we review the scientific literature on metalloAMPs that enhance their antimicrobial efficacy when combined with the essential metal ion zinc(II). Beyond the role played by Zn(II) as a cofactor in different systems, it is well-known that this metal ion plays an important role in innate immunity. Here, we classify the different types of synergistic interactions between AMPs and Zn(II) into three distinct classes. By better understanding how each class of metalloAMPs uses Zn(II) to potentiate its activity, researchers can begin to exploit these interactions in the development of new antimicrobial agents and accelerate their use as therapeutics.
EPrint Processing Status: Full text deposited in DRO